Characteristics of plexiform ameloblastoma patients at dr. Hasan Sadikin Hospital OMFS Department, 2020-2024 - Gideon Ferry Hadinata Pasaribu; Harmas Yazid Yusuf; Melita Sylvyana; Rani Septrina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Ameloblastoma, the most prevalent odontogenic tumor (40–50% of occurences worldwide), displays locally aggressive characteristics and a significant recurrence rate after incomplete excision, predominantly in the posterior mandible. Population studies show differences in histopathology and demographics. The follicular subtype is the most common, and 60–80% of people who have conservative treatment will have a recurrence. While the characteristics of the plexiform variant require elucidation, aggressive resection mitigates risk. This study examines the location, management, histopathology, and demographics of plexiform ameloblastoma cases at the oral surgery department of Hasan Sadikin Hospital between 2020 and 2024.Method: A retrospective analysis utilized the medical records of patients diagnosed with plexiform-type ameloblastoma. We looked at 41 cases and looked at things like age, gender, where the tumor was, what treatment was given, and how often it came back.Result: The majority of the patients were between the ages of 21 and 30 (29.3%), with an average age of 37. More than half of them were women (53.7% vs. 46.3%). The mandible was involved in 92.7% of cases, mostly in the back. Segmental resection (39.0%) and hemimandibulectomy (39.0%) were the most common radical surgeries. Patients who received radical treatment did not exhibit any recurrences during follow-up; cases managed conservatively (enucleation/curettage) are currently under observation. Conclusion: This study emphasizes the necessity for appropriate management of plexiform-type ameloblastoma to reduce the likelihood of recurrence and enhance patients' quality of life. Consequently, additional research involving larger sample sizes and extended follow-up durations is essential to assess the recurrence risk and the efficacy of each treatment modality.